Self-acceptance and sexual disorientation in adolescents: integrating Ibn Miskawaih’s al-dini al-‘aqlani and humanistic Islamic educational psychology - Amalia, Alfita Choirun; Ni’mah, Musbirotun; Wijayanti, Catur Lestari; Ahbab, A. Nasih; Abu Bakar , M. Yunus (Jurnal Pendidikan Agama Islam Al-Thariqah, 2026)
This study aims the relevance of Ibn Miskawaih's concept of al-dīnī al-'aqlānī in understanding self-acceptance among Muslim adolescents experiencing sexual disorientation. Using a phenomenological qualitative approach, data were collected through in-depth interviews and analyzed through reduction, categorization, and meaning interpretation within the tazkiyatun nafs framework. The findings reveal that sexual disorientation generates profound tension between self-acceptance needs and religious guilt, yet religiosity can serve as a constructive spiritual resource when freed from social judgment. The novelty of this study lies in its transdisciplinary integration of Ibn Miskawaih's tazkiyatun nafs with humanistic self-acceptance theory a synthesis previously untheorized in Muslim adolescent identity counseling, proposing that spiritual happiness (sa'ādah) is inseparable from the balance between rationality, morality, and mental health. This integration reframes religion not as a source of moral pressure, but as a private reflective space supporting emotional regulation. These findings recommend a spiritual-humanistic mentoring model for Islamic education and counseling settings, with implications for developing empathetic, non-discriminatory character education strategies for adolescents with diverse identity backgrounds.